2023
DOI: 10.1002/chem.202203608
|View full text |Cite
|
Sign up to set email alerts
|

Dispersibility of TiO2 Nanoparticles in Less Polar Solvents: Role of Ligand Tail Structures

Abstract: Nanoparticles (NPs) are inherently prone to aggregation and loss of their size‐derived properties, thus it is essential to enhance their dispersibility for applications. In less polar solvents, organic ligands containing oleyl groups are known as good dispersants due to their inefficient shell packing and inhibition of chain–chain crystallization as well as interdigitation between adjacent NPs. However, reagents with oleyl structures, such as oleic acid and oleylamine, can contain trans double bonds and satura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…Recent detailed studies of organic ligands have revealed that a slight difference in the molecular structure of aliphatic ligands significantly affects the dispersibility of the NCs. 10–13 Moreover, it has also been reported that the dispersibility and emission properties of NCs are altered by changing the primary, secondary, and tertiary structures of the phosphonic acids and thiols. 14 However, there are few examples that reveal the effect of the molecular structure of alkyl ligands on the excited-state dynamics of NCs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent detailed studies of organic ligands have revealed that a slight difference in the molecular structure of aliphatic ligands significantly affects the dispersibility of the NCs. 10–13 Moreover, it has also been reported that the dispersibility and emission properties of NCs are altered by changing the primary, secondary, and tertiary structures of the phosphonic acids and thiols. 14 However, there are few examples that reveal the effect of the molecular structure of alkyl ligands on the excited-state dynamics of NCs.…”
Section: Introductionmentioning
confidence: 99%